A Late Miocene Terrestrial Temperature History for the Northeastern Tibetan Plateau's Period of Tectonic Expansion - Chihao Chen; Yan Bai; Xiaomin Fang; Haichao Guo; Qingquan Meng; Weilin Zhang; Pengchao Zhou; Azamdzhon Murodov (Geophysical Research Letters)
Abstract During the Late Miocene, the climate patterns and ecosystems of continental land masses experienced crucial transitions, but whether the principal driver was regional tectonic forcing or a decline in CO2 concentrations remains debated. Here we present a terrestrial paleotemperature record spanning ~12.7–5.2 Ma based on tetraether lipids extracted from the northeastern Tibetan Plateau. Our results reveal a sharp cooling (~8 °C) during ~10.5–8 Ma, asynchronous with minor fluctuations in global sea temperatures, suggesting a rapid tectonic uplift of ~1 km in extent. This event appears consistent with the simultaneous aridification and transitions of ecosystems experienced in adjacent regions. Moreover, the amplitude of the cooling over land is less than that which occurred over the ocean during the CO2‐dominated Late Miocene cooling event (~7–5.4 Ma). We therefore concluded that tectonic forcing, rather than a decline in CO2 levels, most likely dominated continental climate patterns and ecosystem transitions during the Late Miocene.